1998
DOI: 10.1021/la9802419
|View full text |Cite
|
Sign up to set email alerts
|

Dicarboxylic Oligopeptide Bolaamphiphiles:  Proton-Triggered Self-Assembly of Microtubes with Loose Solid Surfaces

Abstract: A new family of oligopeptide-based bolaamphiphiles, glycylglycine-(1a-h), glycylglycylglycine-(2a-b), sarcosylsarcosine-(3), L-prolyl-L-proline-(4), glycylsarcosylsarcosine-( 5), and glycyl-L-prolyl-L-proline (6)based bolaamphiphiles with a dicarboxylic headgroup at each end, has been synthesized. The oligopeptide fragments were linked via amide bond to a long-chain R,ω-dicarboxylic acid as a hydrocarbon spacer. Self-assembling properties of these bolaamphiphiles in water have been studied by light and cryogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
203
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 217 publications
(213 citation statements)
references
References 36 publications
10
203
0
Order By: Relevance
“…Details of this bolaamphiphile peptide monomer synthesis and the nanotube self-assembly have been described (50,54,55). The HG12 peptide was sequenced by Applied Biosystems Peptide Synthesizer 432A and purified by using Beckman 110 HPLC equipped with a C-18 reverse-phase chromatographic column at the Center for Study of Gene Structure and Function, City University of New York.…”
Section: Methodsmentioning
confidence: 99%
“…Details of this bolaamphiphile peptide monomer synthesis and the nanotube self-assembly have been described (50,54,55). The HG12 peptide was sequenced by Applied Biosystems Peptide Synthesizer 432A and purified by using Beckman 110 HPLC equipped with a C-18 reverse-phase chromatographic column at the Center for Study of Gene Structure and Function, City University of New York.…”
Section: Methodsmentioning
confidence: 99%
“…N-Acyl amino acid surfactants, which are anionic amino acid-type surfactants, are useful both from industrial and domestic viewpoints, because of their biodegradability and low toxicity. Further, concern over the effect of the residues on aggregation has been growing since it was reported that some amphiphiles containing peptide groups like N-acyl amino acid, self-assembled to form various highly-organized nanometer-scale structures [20][21][22][23]. Since micelle formation is one of the most basic of aggregation behavior, it is useful to investigate the effect of amino acid residues for the purpose of understanding the higher self-assembly behavior, including that of polypeptides [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…55 To the contrary, although from the same family, oligoglycine-based bolaamphiphiles that possess carboxylic (instead of amino) head groups do not assemble as tectomers but as vesicles and microtubes, because of the electrostatic repulsion between ionized carboxylic groups. 56,57 Tectomers have the ability to form extensive, surface adaptive, ultrathin coatings and, on top of that, are biocompatible and may act as biointerfaces. This, together with the atomically smooth rigid 2D structure (which is very unique to this system), pH-responsive nature and chemical reactivity of their terminal amino groups are attributes that make tectomers very appealing as platforms for engineering novel functional layered biomaterials.…”
Section: Introductionmentioning
confidence: 99%